Extracellular Matrix-Associated Protein Sc1 Is Not Essential for Mouse Development - McKinnon, Peter J. (American Society for Microbiology, 2000)
Sc1 is an extracellular matrix-associated protein whose function is unknown. During early embryonic development, Sc1 is widely expressed, and from embryonic day 12 (E12), Sc1 is expressed primarily in the developing nervous system. This switch in Sc1 expression at E12 suggests an importance for nervous-system development. To gain insight into Sc1 function, we used gene targeting to inactivate mouse Sc1. The Sc1-null mice showed no obvious deficits in any organs. These mice were born at the expected ratios, were fertile, and had no obvious histological abnormalities, and their long-term survival did not differ from littermate controls. Therefore, the function of Sc1 during development is not critical or, in its absence, is subserved by another protein.